Frailty Prevalence in Younger End-Stage Kidney Disease Patients Undergoing Dialysis and Transplantation - Chu, Nadia M; Chen, Xiaomeng; Norman, Silas P; Fitzpatrick, Jessica; Sozio, Stephen M; Jaar, Bernard G; Frey, Alena; Estrella, Michelle M; Xue, Qian-Li; Parekh, Rulan S; Segev, Dorry L; McAdams-DeMarco, Mara A (American journal of nephrology, 2020)
Frailty, originally characterized in community-dwelling older adults, is increasingly being studied and implemented for adult patients with end-stage kidney disease (ESKD) of all ages (>18 years). Frailty prevalence and manifestation are unclear in younger adults (18-64 years) with ESKD; differences likely exist based on whether the patients are treated with hemodialysis (HD) or kidney transplantation (KT). We leveraged 3 cohorts: 378 adults initiating HD (2008-2012), 4,304 adult KT candidates (2009-2019), and 1,396 KT recipients (2008-2019). The frailty phenotype was measured within 6 months of dialysis initiation, at KT evaluation, and KT admission. Prevalence of frailty and its components was estimated by age (≥65 vs. <65 years). A Wald test for interactions was used to test whether risk factors for frailty differed by age. In all 3 cohorts, frailty prevalence was higher among older than younger adults (HD: 71.4 vs. 47.3%; candidates: 25.4 vs. 18.8%; recipients: 20.8 vs. 14.3%). In all cohorts, older patients were more likely to have slowness and weakness but less likely to report exhaustion. Among candidates, older age (odds ratio [OR] = 1.79, 95% CI: 1.47-2.17), non-Hispanic black race (OR = 1.30, 95% CI: 1.08-1.57), and dialysis type (HD vs. no dialysis: OR = 2.06, 95% CI: 1.61-2.64; peritoneal dialysis vs. no dialysis: OR = 1.78, 95% CI: 1.28-2.48) were associated with frailty prevalence, but sex and Hispanic ethnicity were not. These associations did not differ by age (pinteractions > 0.1). Similar results were observed for recipients and HD patients. Although frailty prevalence increases with age, younger patients have a high burden. Clinicians caring for this vulnerable population should recognize that younger patients may experience frailty and screen all age groups.